Experimental poisoning by the burs of Xanthium cavanillesii (Asteraceae) in cattle Intoxicação experimental pelos frutos de Xanthium cavanillesii (Asteraceae) em bovinos - Colodel E.M. (2000)
The ground burs of Xanthium cavanillesii Schouw were force fed to 11 calves in single or repeated doses. Quantities of 5 g/kg and above were lethal and 4 animals died. A single dose of 3 g/kg caused moderate clinical signs in 1 calf. Weekly doses of 3 g/kg and 5 g/kg fed to 2 calves during 4 weeks and 2 weeks, respectively, did not cause poisoning. Hypoglicemia and increased levels of aspartate aminotransferase (AST) were detected only in the animals that showed clinical signs. These were observed between 7 hours and 12 hours after the beginning of the administration of the burs and included apathy, excessive salivation, generalized muscle tremors, trismus, diffuse sweating and decreased rate and intensity of ruminal movements. Locomotor disturbances consisted of stiff and incoordinated gait, unwillingness to move, and recumbency. In the terminal stages, there were convulsive seizures, paddling movements, muscle spasms, apnea and death. One animal recovered from the disease. In this case, the clinical picture was similar to the one of the animals that died, although less intense. The first signs were observed 18 hours after the beginning of the administration and lasted 72 hours. Liver biopsies from that animal revealed coagulative hepatocellular necrosis associated with congestion and hemorrhages. The degenerative and necrotic hepatocellular changes were less intense with longer evolution of the clinical picture. In the calf that died, microscopic lesions were observed in liver biopsies 12 hours after the beginning of administration. Serum analysis releaved decreased glucose levels and increased aspartate aminotransferase seric activity. Main necropsy findings included accentuation of the lobular pattern of the liver and marked edema of the gall bladder wall and in adjacent tissues. The contents of omasum and rectum were dried up. There was also ascites, and disseminated petechiae and ecchymoses on serous membranes. The main histopathological changes consisted of marked coagulative hepatocellular necrosis which varied from centrilobular to massive, and was associated with congestion and hemorrhage. In the remaining of the hepatic lobule there was either swelling or vacuolation of the hepatocytes.